Precision Measurement of the Boron to Carbon Flux Ratio in Cosmic Rays from 1.9 GV to 2.6 TV with the Alpha Magnetic Spectrometer on the International Space Station - M. Aguilar; L. Ali Cavasonza; G. Ambrosi; L. Arruda; N. Attig; S. Aupetit; P. Azzarello; A. Bachlechner; F. Barao; A. Barrau; L. Barrin; A. Bartoloni; et al. (American Physical Society, 2022)
Knowledge of the rigidity dependence of the boron to carbon flux ratio (B/C) is important in understanding the propagation of cosmic rays. The precise measurement of the B/C ratio from 1.9 GV to 2.6 TV, based on 2.3 million boron and 8.3 million carbon nuclei collected by AMS during the first 5 years of operation, is presented. The detailed variation with rigidity of the B/C spectral index is reported for the first time. The B/C ratio does not show any significant structures in contrast to many cosmic ray models that require such structures at high rigidities. Remarkably, above 65 GV, the B/C ratio is well described by a single power law RΔ with index Δ = −0.333 +/- 0.014(fit) +/- 0.005(syst), in good agreement with the Kolmogorov theory of turbulence which predicts Δ = −1/3 asymptotically.